Bridging the "Pacific Divide" sociocultural factors that influence the socialization experiences of Filipino immigrant families in San Francisco - Del Rosario, Cecilia Palma (ProQuest Information and Learning Company, 2003)
This study investigates significant factors that influence the manner in which Filipino immigrant parents socialize their children for successful membership in the primary sociocultural context of the home which can differ substantially from the context in which the family lives--American society. These factors include: (1) Ethnic Identity/Cultural Orientation; (2) Personal beliefs regarding Parental Roles/Family Relationships; (3) Parental descriptions of the "Modal Filipino Person"; (4) Language Option and Usage; and (5) Perceived Discrimination and "Colonial Mentality." 100 mothers with children who were enrolled in San Francisco public schools answered a 25-item survey. In-depth interviews were also conducted with selected parents to further explore the confluence of sociocultural factors and personal choices on this all-important parenting task. Findings from the survey and interview reveal that the socialization goals of many Filipino immigrant mothers in the San Francisco Bay Area are highly influenced by traditionally defined and culturally desired child-rearing practices. However, the findings also reveal problems faced by parents as they try to socialize their children according to their 'heritage culture' in the midst of pressures to acculturate and assimilate to a host society that espouses differing and opposing values. This plus their status as former U.S. colonists, immigrant minorities, and people of color influence the degree to which they are able to remain faithful to traditional child-rearing goals and practices. Whereas some are able to succeed in socializing their children in traditional ways, many others often find themselves redefining their child-rearing notions, reconfiguring familial roles, and re-examining their expectations vis-a-vis their children's development of cultural identities, preservation of traditional values, and loss or maintenance of their native language. In light of these findings, it is important to realize that the family plays a key role in the overall acculturative experience of immigrant children. Therefore, educational, social, local, and national institutions from both the sending and receiving countries should support Filipino immigrant families as they help their children to become active designers of their 'social futures' and proactive members of a multicultural society that they now call their own--successful in their efforts at becoming culturally adapted yet holding fast to their identities as uniquely Filipino American.